Effect of outsourcing strategies on the performance of small and medium scale enterprises (SMEs) - John I. Agburu; Nyianshima Calvin Anza; Akuraun Shadrach Iyortsuun (Journal of Global Entrepreneurship Research, 2017)
Several organizations have embarked on outsourcing strategies over the years but many still suffer in terms of their goal achievement; some have experienced low productivity both in terms of quality and quantity, their profitability has not been stable, and their capacities are grossly underutilized. This research work determined the effect of outsourcing strategies (back office activities, primary activities, accounting activities and supporting activities) on the performance of Small and Medium Scale Enterprises (SMEs). Survey research design was adopted in Benue State, Nigeria. Stratified random sampling technique was used in selecting respondents for a primary source data gotten through a well-designed and self-administered questionnaire. Also, secondary data was sourced from the financial records of ten (10) selected SMEs. The variables were statistically analyzed using multiple regression technique. At the end of the research, the study found that; outsourcing of back office activities (such as bookkeeping, payroll, billing, order processing, payment processing, cleaning services, security services and other administrative activities); outsourcing of primary activities (such as manufacturing, purchases, warehousing, Sales force and customer service); outsourcing of Supporting activities(such as shipping, IT services/system, training, advertising, legal services, transport services, public relations) has a significant effect on organizational profitability of SMEs whereas, outsourcing of accounting activities(such as financial reporting, tax processing) has no significant effect on performance of SMEs. This study therefore recommended that SMEs should embark more on outsourcing strategies to attain the benefits of cost savings/restructuring which results in better customer service at profit; also, outsourcing process management through follow up steps like effective communication and monitoring should be employed and taken seriously to better reap the benefits of this maintenance/growth strategy. Also, SMEs should ensure that, the costs of managing the outsourcing process is not greater than the benefits generated by the outsourcing program.
Keywords: 650; Outsourcing strategies; Performance and small and medium scale enterprises